Secure gateway for Internet of Things with internal AAA mechanism - Samociuk, Dominik; Adamczyk, Błażej (Theoretical and Applied Informatics, 2016)
In this paper, we describe secure gateway for Internet of Things (IoT) devices with internal AAA mechanism, implemented to connect IoT sensors with Internet users. Secure gateway described in this paper allows to (1) authenticate each connected device, (2) authorise connection or reconguration performed by the device and (3) account each action. The same applies to Internet users who want to connect, download data from or upload data to an IoT device. Secure Gateway with internal AAA mechanism could be used in Smart Cities environments and in other IoT deployments where security is a critical concern. The mechanism presented in this paper is a new concept and has been practically validated in Polish national research network PL-LAB2020.
Keywords: Internet of Things; security; AAA mechanism